2021
DOI: 10.3389/fpls.2021.745422
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Development of Salt Glands, Stomata, and Pavement Cells in Limonium bicolor

Abstract: Salt-resistant plants have different mechanisms to limit the deleterious effects of high salt in soil; for example, recretohalophytes secrete salt from unique structures called salt glands. Salt glands are the first differentiated epidermal structure of the recretohalophyte sea lavender (Limonium bicolor), followed by stomata and pavement cells. While salt glands and stomata develop prior to leaf expansion, it is not clear whether these steps are connected. Here, we explored the effects of the five phytohormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Salt glands were already described in classical plant anatomy studies [38], but recent research sheds light on their evolutionary origin and the physiological, biochemical and molecular mechanisms of salt secretion through salt glands [19,20,34,36,39]. There are many reports on the structure and function of salt glands in the genus Limonium [34,[40][41][42][43][44] due to its large number of species, many of them endemics, adapted to saline or dry environments.…”
Section: Discussionmentioning
confidence: 99%
“…Salt glands were already described in classical plant anatomy studies [38], but recent research sheds light on their evolutionary origin and the physiological, biochemical and molecular mechanisms of salt secretion through salt glands [19,20,34,36,39]. There are many reports on the structure and function of salt glands in the genus Limonium [34,[40][41][42][43][44] due to its large number of species, many of them endemics, adapted to saline or dry environments.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that the generation of bracelet salt glands might be under long‐term regulation by a phytohormone. As we previously did not observe any bracelet salt glands following treatment with various plant hormones such as gibberellin, brassinolide, and salicylic acid (Gao et al, 2021), we asked whether cytokinin (6‐BA) might induce bracelet salt gland formation, as this plant hormone was not tested in our previous study.…”
Section: Resultsmentioning
confidence: 99%
“…The exogenous application of a certain concentration of methyl jasmonate (MeJA) also increased the density of salt glands and salt secretion (Yuan et al, 2018b). Therefore, plant hormones are expected to influence the development of salt glands (Gao et al, 2021), although typical plant hormones, such as cytokinins, have not been reported to participate in this process. The transcription factors TRANSPARENT TESTA GLABRA1 (LbTTG1) and basic Helix-loop-helix (LbHLH) contribute to salt gland development of L. bicolor based on results obtained from CRISPR (clustered regularly interspace short palindromic repeats)/Cas9 (CRISPR-associated nuclease 9)-mediated gene editing and overexpression studies (Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Salt glands are a typical salt secretory epidermal structure that are present in 68 species, including sea lavender ( L. bicolor ) ( Li et al., 2020 ; Lu et al., 2020 ). L. bicolor belongs to the Plumbaginaceae ( Yuan et al., 2016a ; Leng et al., 2018 ; Yuan et al., 2018 ; Leng et al., 2019a ; Leng et al., 2019b ; Guo et al., 2020b ; Gao et al., 2021 ) and is a unique recretohalophyte with a sequenced genome that constitutes an essential genetic resource for improving salt tolerance in crops. Salt gland differentiation is the earliest visible sign on the epidermis, even before the development of stomata and other epidermal structures.…”
Section: Introductionmentioning
confidence: 99%